2006
DOI: 10.1163/156856106778456609
|View full text |Cite
|
Sign up to set email alerts
|

The effect of grafted caged silica (polyhedral oligomeric silesquioxanes) on the properties of dental composites and adhesives

Abstract: With the emergence of commercial grafted caged silica (Polyhedral Oligomeric Silesquioxanes, POSS) having a three-dimensional (3D) morphology with peripheral functionality, new opportunities have been created for formulating dental adhesives and composites with enhanced mechanical and physical properties. The objective of the present study was to investigate the properties obtained by incorporating grafted caged silica into acrylate based dental composite and adhesive systems. Two commercial POSS materials (me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…An increased roughness leads simultaneously to a reducing of the thermal properties, especially the value of T g , according with the results obtained by Dodiuk et al23, 24 This statement confirms the T g results recently reported by our team 16…”
Section: Resultssupporting
confidence: 91%
“…An increased roughness leads simultaneously to a reducing of the thermal properties, especially the value of T g , according with the results obtained by Dodiuk et al23, 24 This statement confirms the T g results recently reported by our team 16…”
Section: Resultssupporting
confidence: 91%
“…Compared with the typical methacrylate‐based resist, the bulk volume shrinkage (∼5.3%) of the typical hybrid resist (JTHC‐a) was lower than that of the methacrylate system (10.6%). The lower shrinkage of our hybrid resist may be due to the thiol–ene photopolymerization18–20 and/or the incorporation of POSS‐SH 33, 47…”
Section: Resultsmentioning
confidence: 99%
“…It was concluded that the mechanical properties of the dental composites were significantly improved by acrylated POSS, but diminished with octaphenyl-grafted POSS, indicating that the chemical functionality of the side-chain groups had a strong influence on the dental materials and their adhesive behaviour. [98] The main obscurity in developing dental materials with low polymer shrinkage rates is the shortfall in mechanical properties to achieve the requirements that are necessary for clinical use. It has been frequently mentioned that POSSmodified polymers can be achieved at relatively low cost and have good processability, toughness, and thermodynamic and anti-oxidative surface properties.…”
Section: Wwwmaterialsviewscommentioning
confidence: 99%